2018
DOI: 10.1126/science.aao4284
|View full text |Cite
|
Sign up to set email alerts
|

A self-assembled nanoscale robotic arm controlled by electric fields

Abstract: The use of dynamic, self-assembled DNA nanostructures in the context of nanorobotics requires fast and reliable actuation mechanisms. We therefore created a 55-nanometer-by-55-nanometer DNA-based molecular platform with an integrated robotic arm of length 25 nanometers, which can be extended to more than 400 nanometers and actuated with externally applied electrical fields. Precise, computer-controlled switching of the arm between arbitrary positions on the platform can be achieved within milliseconds, as demo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
303
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 343 publications
(306 citation statements)
references
References 62 publications
1
303
0
2
Order By: Relevance
“…Thus, the full potential of self-assembled hierarchical cellulose materials is yet to be reached, as studying and understanding single particles at different length scales is paramount for rational material design. [17][18][19][20] In spite of its potential, precisely self-assembled cellulose nanostructures and materials are still to be realized, due to the lack of detailed understanding of the mechanisms ruling mesoscopic structures. [15][16][17] This has enabled the recent development of an impressive amount of DNA-based applications and technologies.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the full potential of self-assembled hierarchical cellulose materials is yet to be reached, as studying and understanding single particles at different length scales is paramount for rational material design. [17][18][19][20] In spite of its potential, precisely self-assembled cellulose nanostructures and materials are still to be realized, due to the lack of detailed understanding of the mechanisms ruling mesoscopic structures. [15][16][17] This has enabled the recent development of an impressive amount of DNA-based applications and technologies.…”
Section: Introductionmentioning
confidence: 99%
“…Electric field directed robotic arm (Left). Reproduced with permission . Copyright 2018, AAAS; real‐time magnetic actuation of DNA nanodevices via modular integration with stiff microlevers (Right).…”
Section: The Development Of Dna Nanotechnologymentioning
confidence: 99%
“…In parallel, as illustrated in Figure (right), many dynamic DNA nanodevices have been constructed in the last three decades . Early studies demonstrated the use of relatively small dynamic units, such as tweezers and switches.…”
Section: The Development Of Dna Nanotechnologymentioning
confidence: 99%
See 1 more Smart Citation
“…The stimuli and energy sources for the operation of such devices can be quite diverse, for instance, DNA strand displacement processes, binding of biomolecules through aptamers, environmental changes (e.g., changes in salt concentrations or physical stimuli such as temperature), or electric and magnetic fields . In many cases, “switchability” has been introduced by appropriate chemical modifications of the devices.…”
Section: Introductionmentioning
confidence: 99%